ANALISIS KEPEMIMPINAN PEJABAT STRUKTURAL PADA DINAS PERINDUSTRIAN DAN PERDAGANGAN KABUPATEN INDRAGIRI HILIR (Studi Pembinaan Human Relations) - Eko Handrian; Arief Rifa'i (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2018)
The Target this research for know level construction of human relations at on duty industry and commerce of sub province of Indragiri downstream. Indicator Assessment cover synchronization there must be the target of organization with target of individual in organization, pleasant job atmosphere, fair informalitas in job relation, subordinate human being is not machine, development of ability of subordinate until maximal level, interesting work and full of challenge, appreciation and confession of execution of duty better, work appliance which enough, place right the on man right the, and recompensation have to be in kind with service which have been given. Research type which is have location at On duty Industry and Commerce Of Sub-Province of Indragiri downstream is descriptive survey, that is priority list quisioner as a means of data collecting and gathered data by means of list quisioner then made material to analyse the condition of empiric of obyektivitas existence of research target at accurate location. There are two population group and of sampel at this research that is structural functionary amount to 25 officer and people amount to 69 people. One sampling technique which is utilized in specifying individual of sampel is census technique for structural functionary and officer. Type and used to data collecting technique consist of, primary data, collected with technique of quisioner, and interview and also data of sekunder collected use observation technique. while technique analyse data the utilized is by utilizing appliance assist the tables of frequency. Pursuant to this technique analyse researcher assess and conclude that leadership of structural functionary at On duty Industry and Commerce Of Sub-Province of Indragiri Downstream ( Study Construction of Human Relations) residing in at interval assessment is enough executed. Recommendation which need to be considered especially with reference to correction of relation which must more hand in glove again to increase organizational effectiveness in running duty and its function.